Book Dedication Pattern in Nursing and Allied Healthcare Sciences: A Bibliometric Study - Koley, Susanta; Ghosh, Papan (Journal of Data Science, Informetrics, and Citation Studies)
This study is based on an analysis of 232 dedication pages, encompassing 581 dedicatees, which were collected by consulting 800 books in nursing and allied health care sciences between 2000 and 2024. This paper tries to set out a quantitative analysis of dedication pages with dedicatees of nursing books through a bibliometric study, and find out types of dedicatees, year wise dedication pattern, trend of dedication, top ranked dedicatees’ relationship designators, chronological distribution of dedications, etc. Parents are often at the top of dedication lists, followed by students, loved ones, children, teachers, spouses, family members, fathers, sons, grandchildren, mothers, nursing professionals, daughters, wives, and others. Some books are also dedicated to former co-authors and publishers also. Additionally, some authors dedicate their books to members of their in-law families, deities, spiritual figures, Mother Teresa, inspirational institutional leaders and managers, readers, or even cherished objects like a beloved doll. Dedications also extend to the nursing profession and clinical professionals, including doctors, nurses, and collaborative peers in human resources including Mother of nursing. They are often devoted to patients, recognizing the tireless efforts of clinical and nursing professionals who spend countless hours caring for them.
Keywords: Dedications; Nursing books; Bibliometric study; Book dedication pattern; Dedicators; Dedicatees; Dedication pages. Relationship designators; Personal dedicatee; Impersonal dedicatee.